Preliminary report on a clutch of six dinosaurian eggs from the upper Triassic Elliot Formation, Northern Orange Free State - Kitching, J. W. (Bernard Price Institute for Palaeontological Research, 1979)
A clutch of six dinosaurian eggs, containing foetal skeletons of as yet uncertain taxonomic affinity, from the Elliot Formation (Red Bed Stage), northern Orange Free State, seems to be the first record of fossil eggs of Upper Triassic age. As preserved the eggs have a long axis of 65 mm, with a short axis of approximately 55 mm. The egg “shell” is exceptionally thin; fragments removed from one of the specimens have an estimated thickness of 0,5 mm. Additional preparation work is at present being undertaken on a reasonably well-preserved skull in one of the eggs and a more detailed description of the specimen and possible parentage will appear at a later date.
Main article
Keywords: Clutch; Eggs; Dinosaur; Free State; Triassic